John's Big Heart In Nicholas Spark's Dear John Novel (2006): A Psychoanalytic Approach - ERMAWATI, Okti; , Drs. Abdillah Nugroho, M. Hum; , Siti Fatimah, S.Pd., M.Hum (2013)
The major problem of this study is how big heart is reflected in Dear John novel by Nicholas Sparks's. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on the psychoanalytic approach. This study is a literary work, which can be categorized into a qualitative study. In this study the researcher uses two data sources, namely primary data and secondary data sources. The primary data source and the object of study is the Dear John novel itself, meanwhile the secondary one is any literature related to this study. The data are collected by searching data through the internet, library and analyzed based on psychoanalytic theory. Based on the analysis, the researcher draws some conclusions. Firstly, the structural elements of the novel have an important role to build up the story so each element cannot be separated from the other. The second is the attitude of big heart by John in the face of problems and accept the fact, make this novel more meaningful. That can be applied in accordance with the psychoanalitic theory.